Role of Electrostatic Interactions in Calcitonin Prefibrillar Oligomer-Induced Amyloid Neurotoxicity and Protective Effect of Neuraminidase - Cariati, Ida (Int J Mol Sci, 2021)
Salmon calcitonin is a good model for studying amyloid behavior and neurotoxicity. Its slow aggregation rate allows the purification of low molecular weight prefibrillar oligomers, which are the most toxic species. It has been proposed that these species may cause amyloid pore formation in neuronal membranes through contact with negatively charged sialic acid residues of the ganglioside GM1. In particular, it has been proposed that an electrostatic interaction may be responsible for the initial contact between prefibrillar oligomers and GM1 contained in lipid rafts. Based on this evidence, the aim of our work was to investigate whether the neurotoxic action induced by calcitonin prefibrillar oligomers could be counteracted by treatment with neuraminidase, an enzyme that removes sialic acid residues from gangliosides. Therefore, we studied cell viability in HT22 cell lines and evaluated the effects on synaptic transmission and long-term potentiation by in vitro extracellular recordings in mouse hippocampal slices. Our results showed that treatment with neuraminidase alters the surface charges of lipid rafts, preventing interaction between the calcitonin prefibrillar oligomers and GM1, and suggesting that the enzyme, depending on the concentration used, may have a partial or total protective action in terms of cell survival and modulation of synaptic transmission.